Implementation of a Servosystem for the control of a dual-purpose nonlinear plant: Inverted Pendulum and Crane. - Rojas Moreno, Arturo (2001)
This article develops design procedures for Proportional Integral Servosystems (abbreviated SS) to control a dual-purpose nonlinear plant: the Inverted Pendulum and Crane (PI&G). Said plant can be described by nonlinear differential equations,where nonlinear terms complicate the modeling and design aspects of the controller.However, based on the linear model of the plant, we can configure discrete SSs by combining controllers with nonlinear observers. Experimental results demonstrate that each SS is capable of stabilizing the PI (or Crane) mounted on a carriage moved by a servomotor. Three configurations of SSs are presented and discussed: an Optimal ControllerSteady State Quadratic (COCEE) with a Quadratic Optimal State Observer (OEOC), a Pole Location Controller (CUP) with a Complete Order State Observer (OEOC), and a CUP with a Minimum Order State Observer (OEOM).